TRAINING OF FUTURE TEACHERS OF MATHEMATICS TO THE FORMATION OF RESEARCH SKILLS OF STUDENTS - Bakhytkul, Kaskatayeva; Asilkhanovna, BATYRBAEVA Gulniet (International Journal of Engineering Technologies and Management Research, 2017)
This article describes the preparation of future teachers of mathematics to the formation of research skills of students. Targeted formation of research skills of students in accordance with the modern model of education of Kazakhstan in the conditions of modernization of secondary education requires: improving the research training of students, ready for effective work in schools. The purpose of the study is to prepare future teachers of mathematics to the formation of research skills of students through solving math problems. The study used research methods as analysis of scientific-methodical and special literature on the research problem; study and analysis of curricula and standards of professional-pedagogical skills, curricula, textbooks and learning materials; pedagogical observation; interview; survey; testing. As a result, students showed willingness to formation of research skills of students through solving math problems. The paper shows methods of solving mathematical problems. The article proposes a solution to the problem of formation of research skills of students on the basis of the decision search task.